2006
DOI: 10.1002/anie.200600831
|View full text |Cite
|
Sign up to set email alerts
|

Water: The Ideal Hydrogen‐Atom Source in Free‐Radical Chemistry Mediated by TiIII and Other Single‐Electron‐Transfer Metals?

Abstract: The authors wish to cite an additional paper. In 2002, Doris and co-workers reported the reduction of a,b-unsaturated ketones in the presence of [Cp 2 TiCl] and MeOH via free-radical chemistry. This observation is closely related to that reported by the authors the same year on the reduction of carbon radicals in the presence of [Cp 2 TiCl] and water but was not cited in the present article. The authors apologize for the oversight. Reference [4] should therefore read as follows: [4] a) b) for related observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(140 citation statements)
references
References 26 publications
6
134
0
Order By: Relevance
“…In fact, we have observed that from some epoxides the main products are allylic alcohols (Scheme 2) instead of the expected deoxygenation products. 7 Thus, an alternative mechanism may be involved. On the basis of kinetic experiments we recently concluded that allylic alcohols cannot derive from a b-hydride elimination processes in bimetallic species such as II.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, we have observed that from some epoxides the main products are allylic alcohols (Scheme 2) instead of the expected deoxygenation products. 7 Thus, an alternative mechanism may be involved. On the basis of kinetic experiments we recently concluded that allylic alcohols cannot derive from a b-hydride elimination processes in bimetallic species such as II.…”
Section: Introductionmentioning
confidence: 98%
“…7 Allylic alcohols are interesting building blocks in organic synthesis. Additionally, the enantioselective synthesis of these compounds might be easily accomplished via this procedure, remembering the fact that enantioenriched oxirane rings can be successfully prepared via well established asymmetric epoxidation reactions developed by Sharpless, Katsuki, Jacobsen, Shi and others.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of a range of epoxides with titanocene(III) chloride and a large excess of water permits the efficient reductive ring opening of the epoxides to give alcohols. 86 The reaction can be performed with a sub-stoichiometric quantity of the titanocene reagent with only a marginal drop in yield. The use of D 2 O allows the selective incorporation of deuterium and confirms the proposed mechanism.…”
Section: )mentioning
confidence: 99%
“…43 The β-titanoxy radicals have been reduced efficiently by different hydrogen atom donors and the regioselectivity towards the less-substituted alcohol has been reported to be high. 44 Chiral pyridyl alcohols have numerous applications, as ligands in asymmetric metal catalysis, 45 as resolving agents 46 or as starting materials for the preparation of more advanced chiral ligands. 47 As one of the first applications of the asymmetric synthesis of diaromatic epoxides, with high stereo-and enantioselectivity, Solladié-Cavallo described the reductive ring opening of 2-pyridyl epoxide 33a and 2-furyl epoxide 34 (Scheme 10).…”
Section: Reductive Ring Openingmentioning
confidence: 99%